A Study on the Relationship Between Consumer Motivations and Subjective Well-Being: A Latent Profile Analysis - Xiao, Jun; Gong, Yanping; Li, Jian; Tang, Xiuyuan; Javeed, Sohail Ahmad; Deng, Yuling (Frontiers in Psychology, 2022)
Consumer motivation plays an important role in their purchase decisions and well-being. Previous studies have investigated the relationship between certain consumer motivations and well-being separately. We aim to employ latent profile analysis (LPA) to explore subgroups of participants who display similar patterns of consumer multiple motivations and to examine differences in subjective well-being across these subtypes. The final group of (N = 1,023, ages 18–58) completed the Consumer Motivation scale online, assessing seven dimensions of consumer motivation. Results of LPA identified four subpopulations of participants: the enthusiastic group has high expectations in all aspects; the balanced group values each aspect of the product but has lower expectations; the rational group emphasizes aspects such as value for money, comfort, and quality; the apathetic group has no strong motivation for consumption, and they are relatively concerned with the dimensions of security, social acceptance, and stimulation. Consumers’ subjective well-being (life satisfaction, positive affect, and negative affect) differed significantly across the four profiles. Specifically, scores for positive affect and life satisfaction were highest in the enthusiastic group, medium in the balanced group, and lowest in the rational and apathetic groups. Scores for negative affect were significantly higher in the enthusiastic and apathetic groups than in the rational group. These findings enable marketers to develop customized marketing strategies for different motivation profiles and contribute to helping consumers with varying motivation profiles to consciously pay attention to their well-being.